Evaluasi Penerapan Sistem Teknologi Informasi Dalam Upaya Meningkatkan Kinerja Kantor Pelayanan Pajak (Studi pada Kantor Pelayanan Pajak Madya Tangerang) - , Yogi Danupatria Krisna, ST ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Public organization is an organization established with the purpose of providing services to the public. This led to a public organization measured its success through the effectiveness and efficiency in providing services to the public. Madya Tangerang Tax Office as a public organization which is oriented to the community trying to provide better service to try and to improve the effectiveness and efficiency of performance with information technology systems. According to Norton and Kaplan in Gaspersz (2005), financial goals is not an appropriate primary goal for the public sector. Governmental organizations measure their success through the ability to regulate a number of budget expenditure on tangible needs of the community, other government agencies and national governments. Wim Van Grembergen (2001) conducted the Balance Scorecard to IT adoption which eventually resulted in the IT-Balanced Scorecard method. Therefore, this study tried to measure the role of information technology systems using IT-Balanced Scorecard, through 4 (four) perspectives, such as financial, customer satisfaction, internal business processes, as well as training and learning. This study examines the results of the implementation by using information technology system to improve the performance of the tax office in financial, customer satisfaction, internal business processes as well as training and learning. Meanwhile, IT problems are challenges ahead for the implementation of IT to work better in accordance with the perspective that has been measured.